Caregiver’s perception towards vocational training among individual with learning disability / Zahidah Haji Abd Aziz - Abd Aziz, Zahidah (2014)
Introduction: Vocational rehabilitation is one of the preparedness programs for employment. The number of people with disable is increasing each year and people with learning disabilities were the highest number of disable person registered in Malaysia (Social Statistic Bulletin of Malaysia, 2012). Besides, the number of unemployment among people with disability is a chronic problem. Based on International Labor Organization (2006) estimate that, the unemployment rate of adults with disability worldwide is 50 percent to 80 percent of disable population. The successful of vocational rehabilitation involve collaboration of individual with disability, vocational rehabilitation counselors, school, teachers, employers and parents (Bellini & Royce-Davis, 1999). However, an overprotective, negative perception and low expectation from caregiver were the main obstacles for the successfulness of vocational training (Murray and Heron, 2003; Shah, Arnold, & Travers, 2004; Lee et al, 2011). Objective: This study is attempts to explore the caregiver’s perception towards transitional program from secondary school to employment of individual with learning disability. Method: A face to face interview was conducted among caregiver who was taking care of individual with learning disability in Selangor and the participants were selected using purposive sampling design. The interview was transcript and emerging themes were identified. Results: The result of the study emphasizes that caregiver has positive perception towards vocational training among individual with learning disability, willing and planning to send LD to the vocational training centre. Discussion: The findings provide interesting insight information specific on perception issues pertaining vocational training encountered by individual with LD. The majority of participants were Male, Malay age between 40 to 49 years old. The interview guideline resulted in five major themes. There was lack of caregiver knowledge and understanding of Learning Disability and Vocational Training. Transition program from school to work emphasize more on schooling than employment. Caregiver has critical role in assist for decision and biggest supporter of financial, physical and psychological to help individual with LD persuit dream to work. Lastly, most of caregiver expected them to be independent in self-care and life and work. Conclusion and recommendation: The result may help to enhance vocational training for individual with LD in Malaysia. The above theme from study have given same areas to be emphasize when introduction of vocational training for an individual with LD done. Due to purposive sampling, the participation views not generalized to the population, hence bigger area of sampling collection is recommended of caregiver with and without LD. Key word: Vocational training, Learning disability, Caregiver perception